Cho biểu thức\(P = \left( {\dfrac{{x - 2}}{{x + 2\sqrt x }} + \dfrac{1}{{\sqrt x + 2}}} \right).\dfrac{{\sqrt x
Cho biểu thức\(P = \left( {\dfrac{{x - 2}}{{x + 2\sqrt x }} + \dfrac{1}{{\sqrt x + 2}}} \right).\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\) với \(x > 0,\,\,\,x \ne 1\).
a) Chứng minh rằng \(P = \dfrac{{\sqrt x + 1}}{{\sqrt x }}\).
b) Tìm \(x\) để \(2P = 2\sqrt x + 5\).
Quảng cáo
a) Chứng minh rằng \(P = \dfrac{{\sqrt x + 1}}{{\sqrt x }}\).
\(\begin{array}{l}P = \left( {\dfrac{{x - 2}}{{x + 2\sqrt x }} + \dfrac{1}{{\sqrt x + 2}}} \right).\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\\P = \left( {\dfrac{{x - 2}}{{\sqrt x \left( {\sqrt x + 2} \right)}} + \dfrac{1}{{\sqrt x + 2}}} \right).\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\\P = \dfrac{{x - 2 + \sqrt x }}{{\sqrt x \left( {\sqrt x + 2} \right)}}.\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\\P = \dfrac{{x + \sqrt x - 2}}{{\sqrt x \left( {\sqrt x + 2} \right)}}.\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\\P = \dfrac{{\left( {\sqrt x - 1} \right)\left( {\sqrt x + 2} \right)}}{{\sqrt x \left( {\sqrt x + 2} \right)}}.\dfrac{{\sqrt x + 1}}{{\sqrt x - 1}}\\P = \dfrac{{\sqrt x + 1}}{{\sqrt x }}\,\,\left( {dpcm} \right)\end{array}\)
b) Tìm \(x\) để \(2P = 2\sqrt x + 5\).
\(\begin{array}{l}2P = 2\sqrt x + 5 \Leftrightarrow 2\left( {\dfrac{{\sqrt x + 1}}{{\sqrt x }}} \right) = 2\sqrt x + 5\\ \Leftrightarrow 2\sqrt x + 2 = \sqrt x \left( {2\sqrt x + 5} \right)\\ \Leftrightarrow 2\sqrt x + 2 = 2x + 5\sqrt x \\ \Leftrightarrow 2x + 3\sqrt x - 2 = 0\,\,\,\left( * \right)\end{array}\)
Đặt \(\sqrt x = t\,\,\left( {t > 0,\,\,t \ne 1} \right)\)
\(\left( * \right) \Leftrightarrow 2{t^2} + 3t - 2 = 0\)
\(\Delta = {3^2} - 4.2.\left( { - 2} \right) = 25 > 0\)
Phương trình có 2 nghiệm phân biệt
\(\begin{array}{l}{t_1} = \dfrac{{ - 3 + \sqrt {25} }}{4} = \dfrac{1}{2}\,\,\left( {tm} \right)\\{t_2} = \dfrac{{ - 3 - \sqrt {25} }}{4} = - 2\,\,\left( {ktm} \right)\end{array}\)
\(t = \dfrac{1}{2} \Rightarrow \sqrt x = \dfrac{1}{4} \Leftrightarrow x = \dfrac{1}{4}\,\,\left( {tmdk} \right)\).
Cách 2: \(2x + 3\sqrt x - 2 = 0\)
\(\begin{array}{l} \Leftrightarrow 2\left( {\sqrt x - \dfrac{1}{2}} \right)\left( {\sqrt x + 2} \right) = 0\\ \Leftrightarrow \left[ \begin{array}{l}\sqrt x - \dfrac{1}{2} = 0\\\sqrt x + 2 = 0\end{array} \right. \Leftrightarrow \left[ \begin{array}{l}\sqrt x = \dfrac{1}{2}\\\sqrt x = - 2\end{array} \right. \Leftrightarrow \left[ \begin{array}{l}x = \dfrac{1}{4}\\x \in \emptyset \end{array} \right.\end{array}\)
Hỗ trợ - Hướng dẫn
-
024.7300.7989
-
1800.6947
(Thời gian hỗ trợ từ 7h đến 22h)
Email: lienhe@tuyensinh247.com